A case study on the factors affecting bankruptcy cases in Malaysia / Siti Hajjar Saabah - Saabah, Siti Hajjar (2015)
The Bankruptcy cases in the country are depending on individual manages their money and prevent from job loss which can make their life troubles. In this study, the researcher wants to investigate the factors that contribute to bankruptcy by using the time series data which is from January 2010 to December 2014 for country of Malaysia. The researcher wants to estimate whether the independent variables are having a relationship with the bankruptcy cases in Malaysia. Finding shows that, only unemployment is significant towards bankruptcy cases in Malaysia, while the other variables there are non-performing loans, households’ wages and credit card debt do not have a significant relationship towards bankruptcy cases in Malaysia. The researcher has used secondary data in the studies. In addition, the researcher also uses Static Ordinary Least Square Method, which consists of Single Linear Regression and Multiple Linear Regression to examine the total bankruptcy of the country. The researcher has chosen to use both methods in order to get the robust result at the end of the models. Finally, I have come out with the conclusion and recommendation to improve bankruptcy cases in the future.